The Effect of Balanced Nutrition Education Using Video and Puzzle on the Level of Knowledge about Nutrition in School-Age Children - Ulfa Shilaisna; Yunisman Roni; Musfardi Rustam (Journal of Education Technology Information Social Sciences and Health, 2025)
School-age children are one of the most vulnerable groups in terms of nutrition. Nutritional problems in school-age children are undernutrition and overnutrition. Nutritional problems that occur in school-age children are caused by a lack of knowledge about the importance of nutritional adequacy. Education is the provision of knowledge about something to increase knowledge. Nutrition education can be provided with attractive media so that information about balanced nutrition can be of interest to school-age children. This study used a quantitative approach using the one group pre test post test method. The sample in the study amounted to 50 6th grade students who were taken using sampling total. The analysis used the Wilcoxon statistical test. After being given education using video and puzzle media on the level of knowledge about nutrition in school-age children, the results showed an increase in mean knowledge between pre and post tests. The mean value before being given balanced nutrition education was 33.24 (SD = 17.146), after being given balanced nutrition education the mean increased to 79.42 (SD = 9.026). The results of the Wilcoxon test analysis show that there is an effect of balanced nutrition education using videos and puzzles with a p value (0.000) < α (0.005). The use of balanced nutrition education using videos and puzzles has an effect in increasing knowledge about nutrition in school-age children at SDN 021 Tanjung Palas